COMMUNICATIVE ILLOCUTIONARY ACT ON STUDENTS’ CONVERSATION VIDEO IN ONE OF THE ENGLISH COURSES IN BANDUNG - Muâ€™man, Muâ€™man (IKIP Siliwangi, 2020)
Speech acts are divided into three categories – locutionary, illocutionary, and perlocutionary. Each speech act can be investigated based on the researcher’s need what it is done in this research purpose of this study aiming to find out the context meaning of communicative illocutionary act categories on students’ conversation video. The spirit of the speech act can be called as illocutionary which becomes a central concept. Regarding to the definition of speech acts, several numerous options related to illocutionary have some kinds of acts such as promising, ordering, and bequeathing. This research uses Austin’s book as a grant theory strengthened by Yule. This research result is the researcher has found communicative illocutionary acts on students’ conversation video including constatives, directives, commissives, and acknowledgments.Keywords: Illocutionary, constative, directives, commissives, acknowledgments